2023
DOI: 10.2147/idr.s406253
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Extensively Drug Resistant Salmonella Enterica Serovar Typhi Clinical Isolates from Lahore, Pakistan

Kokab Jabeen,
Sidrah Saleem,
Shah Jahan
et al.

Abstract: Background The emergence of extensively drug-resistant (XDR) typhoid in Pakistan has endangered the treatment options available to manage this infection. Third generation cephalosporin were the empiric choice to treat typhoid fever in Pakistan, but acquisition of ESBLs have knocked them out of the arsenal. The current empiric choice is azithromycin which is vulnerable to resistance too. This study aimed to assess the burden of XDR typhoid and the frequency of resistance determinants in blood cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Additionally, the H58 strain co-existed with XDR-S. Typhi, along with the gyrA, gyrB, blaCTX-M-15, and blaTEM-1 genes. A study conducted in Hong Kong found that 30 strains originating from southeast Asia displayed the H58 haplotype in XDR-S. Typhi In addition, a study conducted in Lahore, Pakistan identi ed the presence of the gyrA, gyrB, blaCTX-M-15, blaTEM, and sul1 genes at the molecular level (Jabeen et al 2023). We investigated the antibacterial activity of manuka honey (+ 24UMF) imported from New Zealand against several MDR and XDR strains of S. Typhi.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the H58 strain co-existed with XDR-S. Typhi, along with the gyrA, gyrB, blaCTX-M-15, and blaTEM-1 genes. A study conducted in Hong Kong found that 30 strains originating from southeast Asia displayed the H58 haplotype in XDR-S. Typhi In addition, a study conducted in Lahore, Pakistan identi ed the presence of the gyrA, gyrB, blaCTX-M-15, blaTEM, and sul1 genes at the molecular level (Jabeen et al 2023). We investigated the antibacterial activity of manuka honey (+ 24UMF) imported from New Zealand against several MDR and XDR strains of S. Typhi.…”
Section: Discussionmentioning
confidence: 99%
“…Initially, cephalosporin and azithromycin were very effective in reducing the severity of typhoid fever caused by quinolone-resistant MDR-S. Typhi. Fluoroquinolones, third-generation cephalosporins and azithromycin are collectively referred to as the second line of antibiotics for the treatment of typhoid fever (Jabeen et al, 2023;Laghari et al, 2019;Rathod et al, 2016). Prudent administration of azithromycin with ceftriaxone allowed some cure for the infection caused by MDR Salmonella (Girgis et al, 1999;Parry, 2004;Parry et al, 2023;Veeraraghavan et al, 2021).…”
Section: His Tory Of Antimicrob Ial Re S Is Tan Ce In Salmon Ell a T ...mentioning
confidence: 99%
“…TEM, SHV and CTX-M are the three major ESBLs found in Enterobacteriaceae that build resistance to the third-generation cephalosporins. The clinical isolate of XDR S. Typhi reported in Pakistan exhibits an abundance of a plethora of resistance genes for the first (bla TEM-1 , sul1, catA1 and dhfR7) and second line (gyrB, gyrA, parC, parE and qnrS) antibiotics as well as the derivatives ofCTX-M ESBLs such as bla CTX-M-U , bla CTX-M-1 , bla CTX-M-15 , bla CTX-M-2 ,bla CTX-M-8 and bla CTX-M-9(Jabeen et al, 2023). The experimental evidences showed the presence of two other ESBLs (SHV and TEM) in the clinical isolates of S. Typhi (purified from blood), which are associated with resistance to ceftriaxone, cefixime and ceftazidime(Ahamed Riyaaz et al, 2018).…”
mentioning
confidence: 99%
“…Typhoid is a systemic febrile disease that can be fatal, which necessitates early antibiotic treatment. It is estimated that there are 14.3 million cases of typhoid worldwide with 128,000 to 161,000 deaths annually [1,2]. The incidence rate of typhoid fever is highest in South Asia, followed by Southeast Asia, Western sub-Saharan Africa, Eastern Sub-Saharan Africa, and Oceania [3].…”
Section: Introductionmentioning
confidence: 99%